Development and validation of attitudes measurement scales: fundamental and practical aspects - Hair, Joseph F.; Gabriel, Marcelo L. D. S.; Silva, Dirceu; Braga Junior, Sergio [UNESP] (Univ Sao Paulo, Fac Economia, 2019)
Purpose - This paper aims to present the fundamental aspects for the development and validation (D&V) of attitudes' measurement scale, as well as its practical aspects that are not deeply explored in books and manuals. These aspects are the results of a long experience of the authors and arduous learning with errors and mistakes. Design/methodology/approach - The nature of this paper is methodological and can be very useful for an initial reading on the theme that it rests. This paper presents four D&V stages: literature review or interviews with experts; theoretical or face validation; semantic validation or validation with possible respondents: and statistical validation. Findings - This is a methodological paper, and its main finding is the usefulness for researchers. Research limitations/implications - The main implication of this paper is to support researches on the process of D&V of measurement scales. Practical implications - Became a step-by-step guide to researchers on the D&V of measurement scales. Social implications - Support researchers on their data collection and analysis. Originality/value - This is a practical guide, with tips from seasoned scholars to help researchers on the D&V of measurement scales.
Keywords: Business research; Scale development; Scale validation; Quantitative methods; Attitude measurement; Attitudes scale